PERILAKU SOSIAL ANAK TUNAGRAHITA SEDANG - Sofinar - - (Jurnal Penelitian Pendidikan Khusus, 2012)
Therefore this study aimed to: 1) Describe the form of social behavior that indicated the child was tunagrahita, 2) Describe the work done in modifying the behavior of the children tunagrahita, and 3 ) Describe the obstacles encountered in modifying children's behavior tunagrahita D.III/C1 class SLB YAPPAT Lubuk Sikaping. This study uses a qualitative descriptive case study approach. Key informants of this study are directly involved in the child's behavior, namely family, school and community. Data derived from observations and interviews. Then analyzed qualitatively. The results showed that: 1) The form of social behavior that indicated the child was Tunagrahita D.III/C1 class include: Egoisi, like the corrupters, not banned, not silent, vengeful, silent, like snacks, easily bored. 2) Obstacles encountered: there is less time for children, not understanding the lack of children, along with her children and too equivocal to the poor behavior of children. 3) modify the behavior of the children tunagrahita Business: Provides an understanding of the child, watching child gestures, in brackets in the room, scolded, giving advice, providing a favorite toy, reward. It is recommended that all the child's environment can influence the child's behavior is such Tunagrahita.